Cancer and its management - Tobias, Jeffrey S.; Hochhauser, Daniel; Souhami, Robert L. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2010)
This edition contains up-to-date information on the molecular classification of lymphomas, reappraisal of the role of surgery and chemotherapy in diseases such as breast cancer, and the increased use of treatment such as haemopoietic growth factors.
Cancer and itsmanagement; Contents; Foreword; Preface; Acknowledgements; Abbreviations; 1 The modern management of cancer: an introductory note; 2 Epidemiology, cure, treatment trials and screening; 3 Biology of cancer; 4 Staging of tumours; 5 Radiotherapy; 6 Systemic treatment for cancer; 7 Supportive care and symptom relief; 8 Medical problems and radiotherapy emergencies; 9 Paraneoplastic syndromes; 10 Cancer of the head and neck; 11 Brain and spinal cord; 12 Tumours of the lung and mediastinum; 13 Breast cancer; 14 Cancer of the oesophagus and stomach.
Revised edition of: Cancer and its management / Robert Souhami, Jeffrey Tobias. 5th ed. 2005.
Includes bibliographical references and index.
Print version record.
Keywords: Cancer -- Treatment; Cancer -- Diagnosis; Neoplasms -- Therapy; Neoplasms -- Diagnosis; Electronic books; Electronic books